THE INFLUENCE OF THE PROBLEM SOLVING GROUP THERAPY AGAINST THE ABILITY OF SOCIAL INTERACTIONS IN SCHIZOPHRENIA PATIENTS OF RSJ - Atika Dewi Rimadhani; Rita Untari (MOTORIK Jurnal Ilmu Kesehatan, 2018)
Background. This research aims to know the influence of the problem solving group therapy against social interaction abilities of patients of schizophrenia. Schizophrenics often shows positive symptoms and negative symptoms. One of the negative symptoms often exhibited by schizophrenic is withdraw (dysfunction social interaction). Negative symptoms (withdrawl) can cause functional dysfunction in people with schizophrenia, such as dysfunction in performing the Activity of Daily Living (ADL), productivity, leisure, cognitive, sensorimotor and psychosocial(social interaction). Methods. This research was conducted on a schizophrenic by the number of respondents 40 people. This research was conducted in Occupational Therapy Rehabilitation Unit RSJ Dr.Radjiman Wediodiningrat, Lawang. Measuring instrument which is used in the form of selfassessement Social Interaction Anxiety Scale (SIAS). This type of research is experimental research. This research using methods of comparative statistical data analysis techniques. The test is used as the analysis of the test of the hypothesis test is parametric that paired sample t test (paired samples t-test) application with the help of SPSS version 17.0.Result. Based on the results of data analysis, the p-value obtained 0.000 (< 0.05), to the extent specified significance of 0.05. It shows that the hypothesis in the studyreceived.Conclusion. Problem solving group therapy effectpatient social interaction abilities against schizophrenia.